2023
DOI: 10.1101/2023.02.23.529651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel adjuvant formulation induces robust Th1/Th17 memory and mucosal recall responses in Non-Human Primates

Abstract: After clean drinking water, vaccination is the most impactful global health intervention. However, development of new vaccines against difficult-to-target diseases is hampered by the lack of diverse adjuvants for human use. Of particular interest, none of the currently available adjuvants induce Th17 cells. Here, we develop and test an improved liposomal adjuvant, termed CAF®10b, that incorporates a TLR-9 agonist. In a head-to-head study in non-human primates (NHPs), immunization with antigen adjuvanted with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…We monitored IFN-γ and IL-17, as CAF01 was shown to induce a strong mixed Th1/Th17 immune response in mice and non-human primates [5], [27]. IFN-γ concentration was variable within each group, but there was a tendency towards CAF23 group producing the highest amounts of IFN-γ, even though two pigs were nonresponders (Fig 1D).…”
Section: Cell-mediated Immune Responses Were Not Polarized By Adjuvan...mentioning
confidence: 99%
“…We monitored IFN-γ and IL-17, as CAF01 was shown to induce a strong mixed Th1/Th17 immune response in mice and non-human primates [5], [27]. IFN-γ concentration was variable within each group, but there was a tendency towards CAF23 group producing the highest amounts of IFN-γ, even though two pigs were nonresponders (Fig 1D).…”
Section: Cell-mediated Immune Responses Were Not Polarized By Adjuvan...mentioning
confidence: 99%
“…Indeed, it was reported that all-trans-retinoic acid administered by intraperitoneal route could enhance the frequency of antigen-specific memory T cells in murine intestine (67). Woodworth et al demonstrated that CAF ® 10b, a liposomal adjuvant administered by intramuscular route, could prime T cells in order to recall them in the lungs or skin using the antigen only administered by intratracheal and intradermal routes in NHP (68). If all-trans-retinoic acid or CAF ® 10b adjuvants are beneficial to induce mucosal tissueresident memory responses, it remains to be confirmed.…”
Section: Optimizing Vaccine Formulationsmentioning
confidence: 99%